Nitrogen effects and genotypic variation in Cd absorption, translocation, and chemical forms in wheat - Wu, Xiaoli; Liu, Miao; Li, Ming; Li, Shizhao; Xiong, Tao; Li, Chaosu; Tang, Yonglu (Frontiers in Plant Science, 2025)
IntroductionReasonable nitrogen (N) and low grain cadmium (Cd) accumulators can effectively reduce grain Cd content in wheat; however, the underlying mechanism remains unclear.MethodsThis study aimed to investigate N effects and genotypic variation in Cd absorption, translocation and chemical forms in low (Chuannong30) and high (Chuanmai88) grain-Cd-accumulating wheat. Pot experiment was arranged in a completely randomized design consisting of two-factors: two soil Cd treatments and six N levels.Results and discussionThe results showed that both genotypes can be grown safely in low-Cd soil under N fertilization rate of 180 kg·ha-1, the low grain-Cd accumulating genotypes can be grown in high-Cd soil under fertilization rates < 135 kg·ha-1, without grain toxicity. Increasing N fertilization improved Cd absorption, translocation and distribution in both genotypes, with a higher effect observed in Chuanmai88, the lower grain Cd content in Chuannong30 may be attributed to low root absorption and translocation from leaf to grain. N fertilization increased almost all Cd chemical forms in the root and leaf, especially under high soil Cd condition, Cd fractions extracted by 80% ethanol were predominant in root and leaf of both genotypes and the concentrations and proportions were also higher in Chuanmai88 than in Chuannong30. Moreover, increasing N fertilization significantly decreased soil pH, increased soil Cd exchange capacity and soil Cd bioavailability, resulting in increased Cd accumulation in plants, Chuanmai88 promoted the activation of the Cd migration in the soil.